Optimalisasi Program Ta’awun dalam Pemberdayaan Ekonomi Umat Berbasis Masjid: - Feri Susanto Susanto; Dedy Rachmad; Ahmad Mukhlis Yusuf (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2023)
The mosque is a special place of worship for Muslims that holds a central and strategic role in religious activities throughout time. Worship varies in forms, such as qauli worship, which is performed with words like reciting the Quran, tasbih, tahmid, and takbir. There are also ritual forms of worship that involve the body, such as prayer, hajj, and umrah. Another form of worship is maaliyyah, which involves donating wealth and possessions to attain the pleasure of Allah Subhanahu Wata’ala (Muhammad Fuad Nassar, 2021). This research aims to assist mosques in enhancing the active participation of congregants in mosque economic empowerment programs using the concept of ta’awun to achieve better outcomes. The goal is to increase the prosperity of more mosques. This research employs a qualitative method. The findings indicate that mosque-based economic empowerment of the ummah using the concept of ta’awun is highly effective.